AI-assisted language learning in education: ESL learners’ perceptions and challenges using ChatGPT / Jenna Desiree Robert, Aries Henry Joseph and Lindey Easter Apolonius - Robert, Jenna Desiree; Henry Joseph, Aries; Apolonius, Lindey Easter (Universiti Teknologi MARA, Kedah, 2025)
Integrating artificial intelligence (AI) into educational settings has generated extensive interest recently. ChatGPT, one of the most recent communication trends in AI, has sparked both interest and criticism in higher education. Researchers have conducted numerous studies on ChatGPT's usage, but further research into using AI collaboratively is needed. One area where AI has shown potential is in assisting students with their tasks. Participants in this study were provided the opportunity to work with their peers in completing their assignment, in accordance with Vygotsky's notion of social interactions for language development. The study’s objective was to perceive the use of ChatGPT as a tool for completing assignments during collaborative work. The focus of the session was to assist the participants in exploring ChatGPT and finding information by using questions as prompts. The data for the study was obtained using a convenience sample method. The descriptive analysis of quantitative survey data was performed using the Statistical Package for the Social Sciences (SPSS) software version 25. The study found that the most important considerations while utilising ChatGPT were providing relevant prompts (questions to assist the search activities) and having a stable internet connection. This study also discovered that users may require further training and support to use ChatGPT's features ethically, as well as to improve their ability to search for information using prompts, which can expedite their search.